A Mobile based Decision Support System for Postural Evaluation of Agricultural Activities with Rapid Entire Body Assessment (REBA) - Sahana M.R.; Shashi Dahiya; Pratibha Joshi; Mukesh Kumar; Alka Arora; Ramasubramanian V. (Journal of the Indian Society of Agricultural Statistics, 2025)
Agriculture is an unorganized sector and it is a very high drudgery prone profession due to the absence of awareness and entry of advanced agricultural technologies. Many farming activities and operations are carried out by farm workers in the agriculture sector, where they are subject to very poor working conditions which can lead to physical and mental stress. Workers in agriculture experience musculoskeletal disorders in various body parts throughout various agricultural operations. These problems are caused by heavy work loads, repetitive movements, uncomfortable postures, prolonged periods of time spent in neutral or unsupported positions and the use of conventional equipment and implements that are not ergonomically built. The ergonomic risk factors present in the workplace can be examined using various evaluation instruments to ascertain the workers abilities and drawbacks. The work-related risks are measured using the scientifically validated posture assessment instruments. Rapid entire body assessment (REBA) is a technique that assess a person’s complete body including wrists, fore arms, elbows, shoulders, neck, trunk, back, legs and knees. It uses a systematic process to find the postural musculoskeletal disorders and risks associated with the job tasks. A mobile application is developed to assess the agricultural activities on the basis of physiological analysis and postural analysis using REBA ergonomics technique. The application evaluates the drudgery involved in the agricultural work by using physical assessment followed by postural ergonomics methods and provide recommendation of correct posture to avoid developing musculoskeletal disorders.